Mediating role of psychological status in the association between resiliency and quality of life among older Malaysians living with knee osteoarthritis - Norman, Siti Sarah; Mat, Sumaiyah; Kamsan, Siti Salwana; Md Ali, Sawal Hamid; Mohamad Yahaya, Nor Hamdan; Chan, Caryn Mei Hsien; Md Ramlia, Dayang Balkis; Mohd Tohitf, Noorlaili; Ibrahim, Norhayati; Shahar, Suzana (TAYLOR & FRANCIS, 2025)
Resilience increases the ability of an individual to overcome adversity.It has not yet been determined how resilience is linked to quality of life among individuals experiencing knee osteoarthritis symptoms. To explore the inter-relationships of psychological distress, resilience and quality of life among older individuals with knee osteoarthritis. The study examined older adults in Kuala Lumpur and Selangor, identifying osteoarthritis through verified physician diagnosis. Various factors, including resilience, psychological status, and quality of life, were measured. In the study with 338 older adults, 50.9% had knee osteoarthritis. Higher resilience was linked to lower depression, anxiety, and stress, and better quality of life in both groups with and without knee osteoarthritis. Psychological factors consistently mediated the link between resilience and quality of life even after controlling potential confounders. Analysis showed that depression, anxiety, and stress mediate the relationship between resilience and quality of life, indicating a significant influence even when considering various factors. Resilience appears to influence psychological well- being and quality of life among older adult with knee osteoarthritis.